Pengembangan Media Pembelajaran Pull Out Photo Box Sebagai Upaya Peningkatan Pemerolehan dan Pembelajaran Bahasa Bagi Anak Berkebutuhan Khusus (ABK) Pada Sekolah Inklusi Tingkat Dasar - Muhammad Aditya Wisnu Wardana; Noerzada Febriana; Yiyin Krida Karina; Slamet Mulyono; Edy Sasmito (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
Abstrack: The process of language acquisition and learning for people with disabilities in inclusive schools needs to be done as an effort to ensure the education of students who study in inclusive classes. At this time Indonesia also has a law on disability equality in various public facilities and places, namely Law Number 8 of 2016. One of the inclusive schools in Indonesia is SDN 3 Kepanjenlor Blitar City. The purpose of developing pull out photo box learning media is one of the efforts to improve language acquisition and learning for children with special needs (ABK) at elementary level inclusive schools. The development of pull out photo box learning media is carried out in 4 stages, namely (1) the define stage; (2) the design stage; (3) the development stage; (4) and the testing stage. This research was conducted by taking samples from educators and students at SDN 3 Kepanjenlor, Blitar City, East Java Province by asking questions to one of the language teaching teachers through the zoom meeting media and students through google form to find out understanding and satisfaction in using pull out photo box learning media in language learning. The results obtained in the study obtained a satisfactory conclusion in using pull out photo box learning media in primary level inclusive classes, namely students are able to understand language learning materials and are interested and active in participating in learning by using this learning media.